2009
DOI: 10.1039/b821209k
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of highly ordered, macroporous Na2W4O13 arrays by spray pyrolysis using polystyrene colloidal crystals as templates

Abstract: Highly ordered, macropore arrays, that is, inverse opal structures, of Na2W4O13 were successfully synthesized by spray pyrolysis using polystyrene (PS) colloidal crystals as templates. A densely packed monolayer of monodisperse PS microspheres was deposited on a silica glass substrate by use of the Langmuir-Blodgett thin film technique. Subsequently, Na2W4O13 layers were deposited on the PS templates as a thin layer by spray pyrolysis of a 5(NH4)2O.12WO(3).5H2O-NaCl solution. The PS templates were, finally, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…A larger surface area increases the number of surface sites available to catalyze the reaction, thus enhancing reactant adsorption and product desorption. Compared to the most common nanostructured TiO 2 , such as the commercial TiO 2 nanoparticles (P25), TiO 2 with modified morphologies, such as nanotubes, [46][47][48][49] nanofibers, 50,51 nanorods, [52][53][54][55] foams, 56,57 and mesoporous structures [58][59][60][61] have larger surface area. It has been demonstrated that the photoconversion efficiency of TiO 2 nanotubes is almost twice that of spherical nanoparticles.…”
Section: Basic Structures Of Tiomentioning
confidence: 99%
“…A larger surface area increases the number of surface sites available to catalyze the reaction, thus enhancing reactant adsorption and product desorption. Compared to the most common nanostructured TiO 2 , such as the commercial TiO 2 nanoparticles (P25), TiO 2 with modified morphologies, such as nanotubes, [46][47][48][49] nanofibers, 50,51 nanorods, [52][53][54][55] foams, 56,57 and mesoporous structures [58][59][60][61] have larger surface area. It has been demonstrated that the photoconversion efficiency of TiO 2 nanotubes is almost twice that of spherical nanoparticles.…”
Section: Basic Structures Of Tiomentioning
confidence: 99%
“…Moreover, it has technological advantages from the viewpoints of its environmentally friendly nature, simplicity and low cost. The diameter of the pore size can be easily controlled in the range from 50 nm to $ 1 mm by changing the sizes of the colloidal spheres [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]. Macroporous structures have been widely studied and fabricated by various techniques, including anodization, lithography, solgel and reactive ion plating [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monodispersed polystyrene and polymethyl methacrylate (PMMA) have been employed to fabricate MCCs [10][11][12]. The principle of NSL is as follows: first, polystyrene (PS) or PMMA MCCs are fabricated on the substrate by self-assembly or spin coating; then, a film is coated on the MCCs by solution casting [13,14], spray pyrolysis [15], electrochemical deposition, or physical vapour deposition, which includes sputtering [16][17][18][19] and subsequent pulsed laser deposition (PLD) [7]. Finally, the MCCs are removed to form a 2D nanostructure.…”
Section: Introductionmentioning
confidence: 99%